THE PROBLEM OF TAX HAVENS AND THE ROMANIAN TAX AUTHORITIES’ REACTION - Mihai-Bogdan Afrăsinei (CES Working Papers, 2013)
The opportunities to avoid paying taxes provided by tax havens have motivated numerous multinational companies to resort to offshore operations, generating a significant tax loss at a global level. Romania is facing the same problem and the Finance Minister estimates that offshore operations in tax havens are approximately between three and four billion Euros. The refusal to exchange information and the lack of transparency of many tax havens represent a barrier for tax authorities to control these transactions and facilitate the coverage of illegal activities. This has determined certain countries, among which Romania, to impose higher taxes on taxable income of non-residents who are residents in “uncooperative” jurisdictions. In this paper we have emphasized the issue of tax havens and we have presented their classification after the foreign contribution to the capital of Romanian companies. We have also listed the ones with which Romania has signed agreements for information exchange.